2006
DOI: 10.1136/gut.2005.076562
|View full text |Cite
|
Sign up to set email alerts
|

Inducible nitric oxide synthase activity contributes to the regulation of peripheral vascular tone in patients with cirrhosis and ascites

Abstract: Background: Overexpression of inducible nitric oxide synthase (iNOS) and increased nitric oxide generation may be associated with the hyperdynamic circulation of patients with cirrhosis. We have, for the first time, used the highly selective iNOS inhibitor, 1400W, to determine whether iNOS activity contributes to the regulation of vascular tone in patients with cirrhosis and ascites. Methods: Bilateral forearm blood flow was measured using strain gauge plethysmography in eight patients with cirrhosis and ascit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 34 publications
2
36
0
Order By: Relevance
“…Among the vasodilators that have been recently implicated in the systemic vasodilatation is nitric oxide, primarily synthesized in the systemic vascular endothelium by nitric oxide synthase [22,23]. In portal hypertension, there seems to be a diminished release of NO from sinusoidal endothelial cells in the cirrhotic liver, whereas in the systemic circulation, there is evidence for an upregulation of the NO synthesis [24].…”
Section: Pathophysiology Of Arterial Vasodilatation and Neurohumoral mentioning
confidence: 98%
“…Among the vasodilators that have been recently implicated in the systemic vasodilatation is nitric oxide, primarily synthesized in the systemic vascular endothelium by nitric oxide synthase [22,23]. In portal hypertension, there seems to be a diminished release of NO from sinusoidal endothelial cells in the cirrhotic liver, whereas in the systemic circulation, there is evidence for an upregulation of the NO synthesis [24].…”
Section: Pathophysiology Of Arterial Vasodilatation and Neurohumoral mentioning
confidence: 98%
“…They showed that iNOS inhibitor causes systemic vasoconstriction in patients with ascites only. This supports the role of iNOS in the circulatory changes associated with cirrhosis [45]. One major factor that plays an important role in promoting NO production is the altered intestinal permeability in patients with advanced liver disease.…”
Section: Systemic and Splanchnic Circulationmentioning
confidence: 64%
“…Previous reports on the pathophysiology of biliary cirrhosis have shown that liver lesions are induced by free radicals [22]. Overproduction of nitric oxide in cirrhosis could lead to the generation of peroxynitrite, a source of oxidative DNA damage [23]. In fact, some researchers have postulated that an increased sister chromatid exchange frequency in human peripheral lymphocytes would contribute to hepatocarcinogenesis as a result of inducing genetic instability [20].…”
Section: Discussionmentioning
confidence: 99%